2012
DOI: 10.1523/jneurosci.0304-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Channel Nav1.7 Is Essential for Lowering Heat Pain Threshold after Burn Injury

Abstract: Marked hypersensitivity to heat and mechanical (pressure) stimuli develop after a burn injury, but the neural mechanisms underlying these effects are poorly understood. In this study, we establish a new mouse model of focal second-degree burn injury to investigate the molecular and cellular basis for burn injury-induced pain. This model features robust injury-induced behavioral effects and tissuespecific altered cytokine profile, but absence of glial activation in spinal dorsal horn. Three voltage-gated sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
89
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 92 publications
10
89
1
Order By: Relevance
“…Furthermore, NaV1.7 has an important role in nerve injury pain. Shields et al [37] reported that NaV1.7 in DRG are implicated in injury-induced neuronal hyperexcitability in a burn-injury model. They suggested NaV1.7-blocking drugs may be effective in burn patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NaV1.7 has an important role in nerve injury pain. Shields et al [37] reported that NaV1.7 in DRG are implicated in injury-induced neuronal hyperexcitability in a burn-injury model. They suggested NaV1.7-blocking drugs may be effective in burn patients.…”
Section: Discussionmentioning
confidence: 99%
“…This model appears suitable for analgesic efficacy profiling of novel treatments that may provide improved management approaches for this under-treated and difficult-to-manage condition. In contrast to previously reported mouse models 187 , this model causes a superficial or first-degree burn, without the presence of blisters or broken skin, while still producing robust mechanical and thermal allodynia as well as detectable differences in weight bearing behaviour.…”
Section: Discussionmentioning
confidence: 64%
“…As Na V 1.7 knockout animals did not develop burn-induced thermal allodynia but exhibited robust burn-induced mechanical allodynia 187 , this chapter further explored the contribution of various Na V isoforms in burn-induced thermal and mechanical allodynia. TTX was examined first in thermal allodynia and was found to be effective, suggesting that TTX-s Na V isoforms are involved in burn-induced thermal allodynia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations